Knowledge, Attitude, and Practice of Voluntary Blood Donation among Medical Doctors at Muhimbili University of Health and Allied Sciences (Tanzania Medical Journal, 2025)
Background: In sub-Saharan Africa, the demand for safe blood and blood products exceeds the available supply. Doctors have the potential to become a donor pool that provides regular supply of safe blood and play a positive role in promoting blood donation at the community level.Broad objective: This study aimed to determine the knowledge, attitude and practice of blood donation among medical doctors at Muhimbili University of Health and Allied Sciences (MUHAS).Methodology: A descriptive cross-sectional study was conducted from June 2022 to August 2022. The study was conducted at MUHAS, a public university in Dar es Salaam, Tanzania. Using multistage cluster sampling, 140 doctors were recruited. Data collection was done using a well-structured self-administered questionnaire; data on sociodemographic characteristics, knowledge, attitude, and blood donation practice was obtained. Knowledge was assessed using six questions, attitude using five questions, and blood donation practice using six questions. Descriptive statistics were generated using SPSS version 20.Results: The median age group of respondents was 30 – 39 years. The male-to-female ratio was 2:1. Most respondents had knowledge about the common blood groups (95%), knowledge of transfusion-transmitted Infections (TTIs) was varied i.e., HIV was known to be a TTI by 95%, HBV by 89.3%, HCV by 75%, Malaria by 40.7% and Syphilis by 56.4% and many respondents were not knowledgeable about the specifics of the donation process including the amount of blood drawn (40%) and the recommended frequency of donation (52.1%). The calculated average of correct responses for knowledge of blood donation was 73.2%. Overall, the attitude towards blood donation was positive (95%), and about half of the study participants reported to have donated blood in their lifetime. However, only 2.9% were regular blood donors. Apart from the self-reported claim of being unfit to donate (24.3%), not being approached to donate was the second most common reason given by the non-donors (18.6%).Conclusion: Our study highlights a discrepancy between having good knowledge and positive attitude towards blood donation, and the actual practice of regular blood donation among medical doctors.Recommendation: We recommend directing efforts toward understanding of barriers to regular blood donation among doctors and developing strategies to increase donor retention.